Egyptian Geoinformatics potentials in Space Science (Egyptian Satellites as a model) - Tamer Amron (The International Journal of Informatics, Media and Communication Technology, 1999)
Throughout the Arab Republic of Egypt, remote sensing and space sciences have witnessed a serious and remarkable development in recent years, and this was represented in the Egypt’s launch a group of satellites with various tasks and at close intervals of time. The nice and wonderful thing is that some of these satellites, and the most recent ones, were made with Egyptian expertise and Egyptian hands as well. This introduces Egypt with strength and competence to the modern fields of space science technology. In addition to that, there is Egypt's ancient history in the field of science, astronomical studies and astronomical observatories, and this is not surprising if we remember the interest and proficiency of the ancient Egyptians in astronomy and remote observation more than 7,000 years ago. Despite this great development witnessed in Egypt in this field recently, there is a rareness in scientific writings that dealt with this Egyptian development, especially in Arabic writings. The majority of these writings focus on studying the American satellites and their versions, or the French, Russian or Chinese ones. The Egyptian satellites did not get the right to introduce them and their characteristics and applications. Perhaps this is due to the recent dates of the production, launch and application of these satellites.